The tribe Phanaeini (Coleoptera: Scarabaeidae: Scarabaeinae) in Peru - Figueroa, Luis (2014)
We examine the occurrence of the tribe Phanaeini (Coleoptera: Scarabaeidae: Scarabaeinae) in Peru based on the collection at Museo de Historia Natural of the Universidad Nacional Mayor de San Marcos and on data provided in literature. Each species is presented with citations of its diagnosis, distribution and related comments. Peruvian Phanaeini includes 30 species in nine genera: Coprophanaeus, Dendropaemon, Gromphas, Oruscatus, Oxysternon, Phanaeus, Sulcophanaeus, Tetramereia and Megatharsis. Oruscatus davus is the only species distributed in the high Andes; Phanaeus lunaris and P. achilles occur in the northern arid zone shared by Peru and Ecuador; the remaining species are Amazonian.